2012
DOI: 10.1073/pnas.1203874109
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation regulates human OCT4

Abstract: The transcription factor OCT4 is fundamental to maintaining pluripotency and self-renewal. To better understand protein-level regulation of OCT4, we applied liquid chromatography-MS to identify 14 localized sites of phosphorylation, 11 of which were previously unknown. Functional analysis of two sites, T234 and S235, suggested that phosphorylation within the homeobox region of OCT4 negatively regulates its activity by interrupting sequence-specific DNA binding. Mutating T234 and S235 to mimic constitutive phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 46 publications
(48 reference statements)
7
81
0
Order By: Relevance
“…39,40 By combining in vitro phosphorylation and phosphoproteomic analyses, we were able to identify several novel putative AKT phosphorylation sites in the OSKM factors with the exception of c-MYC. For OCT4 we confirmed not only the previously reported AKT phosphorylation site T235, 29,33 but also found new phosphorylation sites at S136, T159, T225 and S236. Likewise, for KLF4 we identified the reported AKT target site at S429 31 as well as novel phosphorylation sites at S19, T33, S234 and S326.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…39,40 By combining in vitro phosphorylation and phosphoproteomic analyses, we were able to identify several novel putative AKT phosphorylation sites in the OSKM factors with the exception of c-MYC. For OCT4 we confirmed not only the previously reported AKT phosphorylation site T235, 29,33 but also found new phosphorylation sites at S136, T159, T225 and S236. Likewise, for KLF4 we identified the reported AKT target site at S429 31 as well as novel phosphorylation sites at S19, T33, S234 and S326.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast to our study, previous in vitro phosphorylation studies used recombinant transcription factors expressed in bacteria. 29,33 Bacterial expression systems exhibit several limitations, because the recombinant proteins are mostly localized in inclusion bodies, requiring protein denaturation and an often inefficient refolding. 34 In line with this notion, we found that several commercial preparations of bacterially expressed OSKM factors lacked robust DNA-binding activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since phosphorylated ERK may initiate rapid proliferation of tumor cells by activating SALL4 after entering cells, high SALL4 expression may be regulated by prostate-specific membrane antigen in prostate cancer (Brumbaugh et al, 2012). Currently, the regulatory effects of SALL4 on the biological functions of prostate cancer cells have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, Thomson's main focus was on phosphorylation of the core pluripotency factors; using improved mass spectrometry, Thomson's group have identified 14 phosphorylation sites in Oct4 and six in Sox2 (Brumbaugh et al, 2012). Phosphorylation at two of the identified sites in Oct4, both of which lie within the homeodomain, decreases Oct4 DNA binding and transcriptional activity.…”
Section: Regeneration Reprogramming and Pluripotencymentioning
confidence: 99%